Development, implementation and evaluation of a clinical research engagement and leadership capacity building program in a large Australian health care service. Issue 1 (December 2016) - Misso, Marie; Ilic, Dragan; Haines, Terry; Hutchinson, Alison; East, Christine; Teede, Helena
Abstract Background Health professionals need to be integrated more effectively in clinical research to ensure that research addresses clinical needs and provides practical solutions at the coal face of care. In light of limited evidence on how best to achieve this, evaluation of strategies to introduce, adapt and sustain evidence-based practices across different populations and settings is required. This project aims to address this gap through the co-design, development, implementation, evaluation, refinement and ultimately scale-up of a clinical research engagement and leadership capacity building program in a clinical setting with little to no co-ordinated approach to clinical research engagement and education. Methods/Design The protocol is based on principles of research capacity building and on a six-step framework, which have previously led to successful implementation and long-term sustainability. A mixed methods study design will be used. Methods will include: (1) a review of the literature about strategies that engage health professionals in research through capacity building and/or education in research methods; (2) a review of existing local research education and support elements; (3) a needs assessment in the local clinical setting, including an online cross-sectional survey and semi-structured interviews; (4) co-design and development of an educational and support program; (5) implementation of the program in the clinical environment; and (6) pre- and post-implementation evaluation and ultimately program scale-up. The evaluation focuses on research activity and knowledge, attitudes and preferences about clinical research, evidence-based practice and leadership and post implementation, about their satisfaction with the program. The investigators will evaluate the feasibility and effect of the program according to capacity building measures and will revise where appropriate prior to scale-up. Discussion It is anticipated that this clinical research engagement and leadership capacity building program will enable and enhance clinically relevant research to be led and conducted by health professionals in the health setting. This approach will also encourage identification of areas of clinical uncertainty and need that can be addressed through clinical research within the health setting.